EFEKTIFITAS DAN EFISIENSI TEKNOLOGI INFORMASI MELALUI TELEWORKING AUDITOR INTERNAL DI MASA PANDEMIC - James Pelupessy (Jurnal Akuntansi dan Pajak, 2022)
The Industrial Revolution 4.0 which is in line with the technological revolution requires human resources to be competent and reliable in the use of technology. These changes have greatly impacted to the work of professional auditors in the midst of a pandemic. Limited physical access, necessities of life and work professionalism are considerations for auditors to continue to carry out auditing online, namely Teleworking. This study is a qualitative descriptive study that aims to assess the effectiveness and efficiency of teleworking in the internal auditor profession during the pandemic. The informants in this study were Maluku provincial government staff who were government internal supervisory staff or APIP. Research data obtained from interviews with four APIP informants offline and online. The results show that teleworking in a pandemic situation is very effective and efficient in the internal auditor profession and the auditor's skills and competencies in mastering digital information technology while still applying audit standards to produce quality audits.